2021
DOI: 10.1101/2021.02.02.429321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endothelial cell senescence exacerbates pulmonary hypertension through Notch-mediated juxtacrine signaling

Abstract: Pulmonary arterial hypertension (PAH) is a fatal disease characterized by pathological pulmonary artery remodeling. Endothelial cells (EC) injury including DNA damage is critically involved in the vascular remodeling in PAH, and persistent injury leads to cellular senescence in ECs. Here, we show that EC senescence exacerbates pulmonary hypertension through Notch-mediated juxtacrine signaling. EC-specific progeroid mice that we recently generated showed exacerbated pulmonary hypertension after chronic hypoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…First, it analyzes all genes rather than differentially expressed genes; second, it is good at detecting modest changes in individual genes by enhancing signal-to-noise ratio [15]. Other studies have found that senescence facilitates in ammation and vascular remodeling in PH [48,49]. A recent study found that Elimination of senescent cells by suicide gene or ABT263 accelerated pulmonary hemodynamics and pulmonary remodeling, decreased PAECs in hypoxia-induces PH, hypoxia + Sugeninduced PH, MCT-induced PH, and mice overexpressing the serotonin transporter [50].…”
Section: Discussionmentioning
confidence: 99%
“…First, it analyzes all genes rather than differentially expressed genes; second, it is good at detecting modest changes in individual genes by enhancing signal-to-noise ratio [15]. Other studies have found that senescence facilitates in ammation and vascular remodeling in PH [48,49]. A recent study found that Elimination of senescent cells by suicide gene or ABT263 accelerated pulmonary hemodynamics and pulmonary remodeling, decreased PAECs in hypoxia-induces PH, hypoxia + Sugeninduced PH, MCT-induced PH, and mice overexpressing the serotonin transporter [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, the functional role of EC glutaminolysis is uncharted to date. Meaningful knowledge might be borrowed from vascular remodeling in pulmonary hypertension, another disease featuring EC senes-cence [311,312]. Bertero et al reported that ECM stiffening increases GLS1 expression and enhances glutaminolytic flux and proliferation in cultured pulmonary arterial ECs [28].…”
Section: Senolysis-therapeutic Targeting Of Senescent Ecs 231 Pharmac...mentioning
confidence: 99%